(untitled) (Medico Legal Update, 2020)
Law No. 11/2012 on the Juvenile Criminal Justice System states that child prisoners in the LPKA (Juvenile Detention Center) are required to participate in the treatment program which consists of personal treatment and independency treatment so that they can come back to their communities well; besides that, they have been prepared with skills. The research problem was how about the treatment model of juveniles who have committed criminal offenses in the LPKA Class 1, Tanjung Gusta, Medan. It is expected that through this research a treatment model of juveniles who have committed criminal offenses in the LPKA can be found in the future. The research used normative and empirical approaches. The data were gathered by conducting interviews with some informants in the Section of Juvenile Treatment of the LPKA Class 1, Tanjung Gusta, Medan, and with the child prisoners. The result of the research showed that personal treatment and independency treatment in the LPKA Class 1, Tanjung Gusta, Medan, were performed with group (classial) and scheduled treatment models. It is recommended that individual treatment model, especially independency treatment be used in the future, and personal treatment should be done by using classial treatment model.